New optimality criteria for convex continuous-time problems of vector optimization. (9th December 2022) - Jović, Aleksandar; Marinković, Boban
Abstract : In this paper, vector continuous-time programming problems with inequality type of constraints are considered. All the results are obtained under convexity assumptions. The main tool employed in the derivation of the zero order optimality conditions is a new version of theorem of the alternative in functional spaces. To apply the alternative theorem, a certain regularity condition must be satisfied. No differentiability assumption is imposed.